The Representation of Orthopaedic Oncology in the Media in Turkey - ŞİRİN, EVRİM; EROL, BÜLENT (My University, 2020)
The effect of the media on decisions taken in healthcare is very strong. To the best of our knowledge, there has been no previous report in literature of how orthopaedic oncology is reflected in the media. In this context, the aim of this study was to present the representation of orthopaedic oncology in the media according to 2019 data. According to the statements of patients presenting at the orthopaedic oncology polyclinic, key words were defined as, bone cyst, bone cancer, bone metastasis, orthopaedic oncology, soft tissue sarcoma, bone cancer treatment, bone cancer symptoms, benign bone tumour, soft tissue cancer. News items presented in the media according to these key words were reviewed with the optical character recognition (OCR) methodology (Ajans Press Group®, Istanbul, Turkey). Screening was applied to almost 4000 newspapers and journals as printed press and more than 10,000 internet sites as the online environment. From the key words screened in the context of this study, there were seen to be a total of 473 news items in newspapers and journals in Turkey in 2019. The news items covered an area of 56310 column centimetres (colcm), and these news items were determined to have reached 44,377,922 people. The advertising equivalent value of the news items was calculated as 2,606,721 TL. The most frequently seen key words in the news items were bone cancer, soft tissue cancer, bone metastasis.These data are shown in detail in the tables. The results of this study, which examined the representation of orthopaedic oncology in the media over a one-year period, showed that half of the news items were in local press, and national representation was low. The field of orthopaedic oncology is poorly represented in the media, and this must be increased for patients to be able to access correct and reliable information.
Keywords: Orthopaedics; Oncology; Media; Media representation